Impaired saccadic adaptation in DYT11 dystonia. Issue 10 (8th March 2011) - Hubsch, Cécile; Vidailhet, Marie; Rivaud-Péchoux, Sophie; Pouget, Pierre; Brochard, Vanessa; Degos, Bertrand; Pélisson, Denis; Golmard, Jean-Louis; Gaymard, Bertrand; Roze, Emmanuel
Abstract : Background: Recent neuroimaging studies point to a possible pathophysiological role of cerebellar dysfunction in dystonia. The authors investigated the association between sensorimotor adaptation, cerebellar dysfunction and the myoclonus–dystonia phenotype. Methods: The authors prospectively analysed reactive saccade adaptation in a genetically homogeneous group of 14 patients with DYT11 dystonia owing to a mutation of the SGCE gene. The authors used a backward reactive saccade adaptation task, a well-characterised experimental oculomotor paradigm involving the cerebellum. The principle of this paradigm is to simulate a spatial error in saccade generation by systematically shifting a visual target during saccade execution. Repetition of this systematic error induces a gradual decrease in the initial saccade amplitude, reflecting an adaptive phenomenon. Results: Saccade adaptation was significantly lower in the DYT11 patients than in healthy controls (mean value: 8.9%±4.5% vs 21.6%±4.5%; p=8.3×10 −6 ). The time course of adaptation also differed between the patients and controls (p=0.002), reflecting the slower saccadic adaptation in the patients. Conclusions: This study provides the first neurophysiological evidence of cerebellar dysfunction in DYT11 dystonia and supports a role of cerebellar dysfunction in the myoclonus–dystonia phenotype.